Current trends in open science - Menichinelli, Massimo (Henry Stewart Talks, 2023)
Free/libre open-source software (FLOSS), Open-source, Creative Commons, Open Research Europe, DIY science, Citizen science, Responsible Research and Innovation (RRI)